Collective Subjectivity: a Theoretical-Methodological Approach (Andamios, Revista de Investigación Social, 2025)
This article presents a theoretical and methodological proposal for the study of social subjectivities from a contemporary perspective. It suggests considering a set of ontological postulates to comprehend the constitution of social order, followed by a category of subjectivity capable of unfolding into functional concepts for research purposes, and finally, a methodological proposal for studying subjectivities within the realm of social sciences.
Keywords: Subjectivity; social ontology; theory of subjectivity; methodology of social sciences